STUDI PERBANDINGAN PERENCANAAN BANGUNAN BAJA SISTEM SPECIAL MOMENT FRAMES DAN SPECIAL PLATE SHEAR WALLS - Sitorus, Deny Anarista; Dewobroto, Wiryanto (Universitas Tarumanagara, 2018)
Indonesia is an earthquake-prone area, therefore, building construction using seismic force resisting system is considered important. Generally, the building structure is reinforced concrete, while steel using the special moment frames (SMF) system is more commonly found as seismic force resisting system. Yet according to ASCE / SEI 7-10 regulations, there are choices of seismic force resisting system for steel buildings such as special plate shear walls (SPSW), special truss moment frames (STMF) and other special systems. This study will show a comparison of SMF and SPSW system building planning in studying the potential use of these two systems in Indonesia. The spatial configuration between columns was chosen to produce a variety of SMF system building designs so as to produce an economical structure. From the results of a comparative study of planning, it is known that the configuration of the building structure with a short span length between columns, the SMF system is more economical when compared to the SPSW system. However, for large span length of span between columns the use of the SPSW system can be an alternative.Keywords: earthquake, special moment frames, special plate shear wallsABSTRAKIndonesia merupakan wilayah rawan gempa, sehingga konstruksi bangunan memakai sistem penahan gaya seismik dianggap penting. Umumnya, struktur bangunan adalah beton bertulang, adapun baja penggunaan sistem special moment frames (SMF) lebih banyak dijumpai sebagai sistem penahan gaya seismik. Padahal menurut peraturan ASCE/SEI 7-10 terdapat pilihan sistem penahan gaya seismik untuk bangunan baja seperti special plate shear walls (SPSW), special truss moment frames (STMF) dan sistem khususnya lainnya. Studi ini akan memperlihatkan perbandingan perencanaan bangunan sistem SMF dan SPSW dalam mempelajari potensi penggunaan kedua sistem ini di Indonesia. Konfigurasi bentang antar kolom dipilih agar menghasilkan variasi desain bangunan sistem SMF sehingga menghasilkan struktur yang ekonomis. Dari hasil studi perbandingan perencanaan, diketahui bahwa konfigurasi struktur bangunan dengan panjang bentang antar kolom yang pendek, maka sistem SMF lebih ekonomis bila dibandingkan terhadap sistem SPSW. Akan tetapi, untuk panjang bentang antar kolom yang besar penggunaan sistem SPSW dapat menjadi alternatif.Kata kunci: gempa, special moment frames, special plate shear walls